Earnings Effects of Household Investment in Health in Colombia - Rocio Ribero (Yale University, Economic Growth Center, 1999)
This study considers the links between primary indicators of health and individual labor productivity in Colombia and explores how additional public expenditures on health may improve individuals' health. Sample statistics how that illness occurs more frequently for women than for men, for less educated than for more educated, for rural than urban residents, and for older individuals. The well educated are considerably taller than those without schooling (6 cm. for males and 4 cm. for females). The empirical evidence confirms that health indicators are related to individual earnings in Colombia. A Mincerain log-earnings equation that includes health indicators as a form of human capital in addition to schooling is specified. When the morbidity variable is treated as endogenous and measured with error and the model is estimated by instrumental variables [IV], it becomes significant and has the expected negative sign. Controlling for age, education, sector of employment, gender and geographic location, an increase by 50% on the average number of days an individual was ill and unable to do his ordinary activities in the last month would imply reductions in labor earnings of 11% for urban males, 8% for urban females, 13% for rural males and 7% for rural females. The estimations with height show a positive sign and high significance even without the IV correction, but the coefficients increased with IV methods by an order of magnitude. Having one more centimeter of stature would increase urban female earns by 4.7% and urban male earnings by 12%. Individual's wealth and living in a community with better health provision indicators are linked with better health outcomes. An analysis of the returns to schooling shows that schooling captures part of the effect of health on productivity when the health indicator is not included in the Mincer equation.
Keywords: I12; J00; J24; 330; Earnings; Height and Health Indicators; Gesundheitskosten; Einkommen; Kolumbien